EFFICIENCY OF USING THE ADAPTED GOAT’S MILK FORMULA IN THE DIET OF HEALTHY YOUNG INFANTS: A MULTICENTER PROSPECTIVE COMPARATIVE STUDY - Тatyana E. Borovik; Natalya N. Semyonova; Olga L. Lukoyanova; Natalya G. Zvonkova; Tatyana V. Bushueva; Tatyana N. Stepanova; Vera А. Skvortsova; Oleg S. Melnichuk; Elena A. Kopyltsova; Elena L. Semikina; Irina N. Zakharova; Irina I. Rjumina; et al. (Вопросы современной педиатрии, 2017)
Background. There is no doubt that it is necessary to study the efficiency of milk formulas that are introduced into the Russian market of baby food. This applies to both new products and known brands of formulas whose composition is subject to change.Objective. Our aim was to assess the clinical efficacy of the adapted goat's milk formula in the diet of young infants.Methods. We conducted a prospective comparative study with healthy full-term  children aged 0–5 months being on a formula (main group) or breast feeding (comparison group). The tolerability of the adapted goat's milk formula, the dynamics of anthropometric indicators, changes in body composition as well as microscopic characteristics  of stool and general clinical and biochemical parameters  of peripheral blood were assessed after 1 month.Results. Good tolerability of the goat's milk formula was noted in 184 (96.8%) of 190 children in the main group. In the course of taking the product, the proportion of children with functional disorders of the gastrointestinal tract decreased significantly from 57 (30%) to 27 (14%) (p < 0.001). Physical development,  complete blood count results, the levels of ferritin, prealbumin and 25(OH)D in children of the main group and the comparison group (n = 71) were comparable and were within the mean age parameters. Qualitative analysis of the level of specific IgE to goat's milk proteins did not reveal any sensibilization in any of the children receiving the milk formula, either at the beginning of the study or after 1 month of taking the product.Conclusion. The studied adapted goat's milk formula can be used in nutrition of young infants in cases of lack or absence of mother's milk.